Advances in Understanding the Pathogenesis of Epstein-Barr Virus-Associated Lymphoproliferative Disorders - Xi Yang (Iranian Journal of Allergy, Asthma and Immunology, 2015)
Epstein-Barr virus (EBV) was discovered 50 years ago from an African Burkitt lymphoma cell line. EBV-associated lymphoproliferative disorders (LPDs) are life-threatening diseases, especially in children. In this article, we review EBV-associated LPDs, especially in the area of primary immunodeficiency disease (PID). We searched PubMed for publications with key words including EBV infection, lymphoma, LPDs and PID, and selected the manuscripts written in English that we judged to be relevant to the topic of this review. On the basis of the data in the literature, we grouped the EBV-associated LPDs into four categories: nonmalignant disease, malignant disease, acquired immunodeficiency disease and PID. Each category has its own risk factor for LPD development. EBV-associated LPD is a complex disease, creating new challenges for diagnosis and treatment.